Register Kelompok Pecinta Burung Berkicau atau Kicau Mania di Kabupaten Boyolali: Kajian Sosiolinguistik (Jurusan Bahasa dan Sastra Jawa Universitas Negeri Semarang, 2022)
Kicau Mania is the mention of a group of songbird lovers. The existence of this group will lead to language registers for fluency in interacting within the group. The register is something that is very interesting to study in groups of songbird lovers in Boyolali because special terms often appear in communication between members of the group. The purpose of this study is to describe the form, meaning, and function of the registers for groups of songbird lovers or Kicau Mania in Boyolali district. This research is a qualitative descriptive study, the source of the data was obtained from the interaction of members of Kicau Mania and event activities in the form of speech from the Kicau Mania group in bird competitions and in bird markets. Methods of data acquisition through field observations and conducting interviews. The techniques applied are tapping, listening and speaking, recording, and taking notes. After obtaining the data, then analyze the data by identifying the data, classifying the data, processing the data and describing the results of the data analysis. This research produced several vocabulary registers, including resik (the mention of female canaries that are ready to mate), kuningan (the mention of young green cucak), kondangan (the mention of losing the competition). In addition, there are also new meanings and vocabulary such as, ngecuske (breeding birds), anggungan (mention of a type of bird that makes a soft voice and buzzes), banggelan (a reference to the term selling fast at a low price). The conclusion of this study is that several registers were found divided according to classification. forms of words and forms of noun phrases, adjectives, and verbs. Then, some meanings of each register vocabulary are obtained which are different from the registers of other language groups. Several special functions were obtained for registering Kicau Mania in Boyolali is heuristic function, informational function, imaginary function, instrumental function, personal function, and interaction function. Keywords: kicau mania; language variation; register